Efforts to Improve Human Resources as Agents of Change in Facing Digital Transformation in Indonesian Islamic Banking - Lia Apriyanti; Aryan Torrido (LPPM Universitas Terbuka, 2024)
The rapid development of technology in the current digital era, where the increasing use of the internet and smartphones in Indonesia means that financial service institutions can utilize digital technology to reach the public. Widely in offering their products or services online. Requiring all service sectors to be supported by quality human resources. However, despite this, the reality is that in the Sharia Banking sector, there is still a lack of quality resources and a comprehensive understanding of Sharia principles. This research method is a method where data collection is carried out by collecting data from various literature. The literature studied is not limited to books but can also include documentation materials, magazines, journals, and newspapers. This research aims to explore Sharia human capital management to improve HR in the Islamic banking environment and try to propose possible solutions to overcome problems related to improving HR performance. These changes can be an opportunity or perhaps a challenge in facing intense competition. Using a qualitative approach. There are at least two significant potential positive impacts that may arise as a result of digital transformation carried out by banking. First, expanding banking accessibility. Second, increase the competitiveness of Indonesian banking. Digital banking will be able to increase ease of access to banking for the public, as well as increase banking efficiency so that it will encourage increased economic activity.